La sociología del acto desviado: la teoría de la anomia y más allá - Cohen, Albert K. (Universidad Nacional del Litoral, 2021)
Merton’s «Social Structure and Anomie» is a large step toward a general theory of deviant behavior. Among the task that remain are: further clarification of the ways in which alter’s experience and adaptations affect ego’s strain and choice of solution; fuller incorporation of the recognition that deviant behavior develops in the course of the interaction process; exploring ways of conceptualizing in the interaction process; and integration of anomie theory with Meadian role theory.